2021
DOI: 10.1371/journal.pone.0250727
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of profitability and resource use efficiency between Penaeus monodon and Litopenaeus vannamei in India

Abstract: The study aimed to highlight the profitability and production function analysis of Penaeus monodon and Litopenaeus vannamei in intensified shrimp farms in Gujarat (India). Two hundred and twenty (220) shrimp farm households were used to identify (principal component and cluster analyses) 8 clusters of management practices that reflected various scales of production intensity ranging from 0–2999 kg/ha/crop to 9000kg/ha/crop and above for both the species. The Cobb-Douglas production function, which relates prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
4
18
1
Order By: Relevance
“…Variable costs accounted for about 88% of total costs across the three farm scales. This is in line with Karim et al (2014) and Nisar et al (2021), who found similar feed cost structures in intensive shrimp production: 91% and 90%, respectively. A significantly higher (p < 0.05) feed cost was found in large farms (USD 11,152 ± 1,200 ha −1 ) than small farms (USD 7036 ± 681 ha −1 ), with feed costs in medium farms (USD 9208 ± 826 ha −1 ) at an intermediate level.…”
Section: Production Costs and Profitabilitysupporting
confidence: 88%
See 3 more Smart Citations
“…Variable costs accounted for about 88% of total costs across the three farm scales. This is in line with Karim et al (2014) and Nisar et al (2021), who found similar feed cost structures in intensive shrimp production: 91% and 90%, respectively. A significantly higher (p < 0.05) feed cost was found in large farms (USD 11,152 ± 1,200 ha −1 ) than small farms (USD 7036 ± 681 ha −1 ), with feed costs in medium farms (USD 9208 ± 826 ha −1 ) at an intermediate level.…”
Section: Production Costs and Profitabilitysupporting
confidence: 88%
“…Electricity and fuels are important inputs in the intensive shrimp production for aeration of ponds. Nisar et al (2021) observed similar findings in intensive shrimp production in India. Lastly, farmers in all three scales reported similar seed, labour, harvesting and marketing and miscellaneous costs (Table 5).…”
Section: Production Costs and Profitabilitysupporting
confidence: 77%
See 2 more Smart Citations
“…As a result, the efficiency of land, water, and energy use in feed-based culture is considerably greater for L. vannamei than for P. monodon (Boyd et al, 2017;Boyd, McNevin, Davis, Godumala, & Mohen, 2018). In feed-based culture, production of L. vannamei also was more than twice as profitable as was production of P. monodon in India (Nisar, Zhang, Navghan, Zhu, & Mu, 2021).…”
Section: Expansionmentioning
confidence: 99%